INNOVATIONS IN CAREER GUIDANCE AND CAREER COUNSELING IN PUBLIC EDUCATIONAL INSTITUTION «KHMELNYTSKYI CENTRE FOR VOCATIONAL EDUCATION IN THE FIELD OF SERVICES» (Innovative professional education, 2025)
Modern innovative approaches to career guidance and career counseling in vocational (vocational and technical) education institutions are considered. It is determined that career guidance and career counseling are necessary elements of preparing young people for professional activity. The prospects for the development of career counseling are outlined, taking into account modern challenges of the labor market.
Keywords: institutions of professional (vocational and technical) education, education seekers, innovations, career guidance, career counseling